2022
DOI: 10.3390/ph15121588
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron Reduces the Incidence of Hypotension after Spinal Anaesthesia: A Systematic Review and Meta-Analysis

Abstract: Hypotension induced by spinal anaesthesia is a common clinical complication associated with multiple perioperative adverse events. We conducted a systemic review and meta-analysis to confirm whether ondansetron could alleviate hypotension following spinal anaesthesia. PubMed, Embase, Web of Science, and Cochrane Library were searched to identify eligible randomised controlled trials from their respective database inception dates to 30 September 2022. The primary outcome of the meta-analysis was the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…The frequency of hypotension in the intervention group was substantially lower than in the control group, indicating that ondansetron effectively mitigates the risk of this common and potentially dangerous side effect. This aligns with previous research, such as the studies by Sahoo et al and El Khouly et al, which demonstrated similar reductions in hypotension with prophylactic ondansetron administration (11,12,14). The study's results are particularly noteworthy in the subgroup analysis, where the difference in hypotension incidence was significant in patients over 26 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of hypotension in the intervention group was substantially lower than in the control group, indicating that ondansetron effectively mitigates the risk of this common and potentially dangerous side effect. This aligns with previous research, such as the studies by Sahoo et al and El Khouly et al, which demonstrated similar reductions in hypotension with prophylactic ondansetron administration (11,12,14). The study's results are particularly noteworthy in the subgroup analysis, where the difference in hypotension incidence was significant in patients over 26 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…Prior to surgical incision, an additional pinprick evaluation at the T4 level was used to assess the adequate level of NA in all patients. All the patients received ondansetron 0.1mg/Kg IV to reduce postoperative nausea and vomiting (PONV) and reduce the incidence of hypotension after spinal anaesthesia [12]. In all patients, sedation was performed during surgery with small bolus injections of intravenous midazolam, up to 5mg, and ketamine 0.15-0.3mg/kg/h.…”
Section: Neuraxial Anaesthesia: Technical Proceduresmentioning
confidence: 99%